Multidimensional Discrete Chaotic Maps - Bucolo, Maide; Buscarino, Arturo; Fortuna, Luigi; Gagliano, Salvina (Frontiers in Physics, 2022)
In this paper, the generalized concept of multidimensional discrete maps is presented. Moreover, a new and fundamental results is shown that remark the invariance of the bifurcation points from periodic to chaotic behavior. Numerical examples regarding the multidimensional cases of the logistic map, the complex-valued Ikeda map and the multivariable Henon map are reported.